Genealogy of knowledge and delegitimization of universities: the pseudo-Paracelsian Aurora philosophorum - Bulang, Tobias (Pseudo-paracelsus, 2022)
Abstract This article introduces the pseudo-Paracelsian treatise Aurora Philosophorum (last third of the sixteenth century) and focusses on the contexts of a specific genealogy of knowledge presented in this text. It reaches from a divine origin of human knowledge to the universities of the author’s times. Here, the transfer of science throughout history is described as a process of continuous decline. The concept of knowledge negotiated by this text is conceptualized not as theory alone: knowledge has a genuine instrumental and practical aspect. The article also presents the principles of the forthcoming edition and commentary of the handwritten and printed copies of the Aurora Philosophorum.
Gesehen am 03.01.2023